2021
DOI: 10.1017/s0373463321000217
|View full text |Cite
|
Sign up to set email alerts
|

Examining drivers’ socio-demographic variables and perceptions towards sanction mechanisms on speeding behaviour on highways: targeting appropriate prevention

Abstract: Investigating the underlying predictors of speeding behaviour deserves the full attention of research. This study aims to examine the effects of demographic variables on the perceived deterrent mechanisms and to predict speeding behaviour to target appropriate prevention programmes. In this study, 212 randomly selected drivers having a valid car driving licence participated in an online survey. The results revealed that demographic variables influenced drivers’ perceptions towards social and legal sanctions as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although the studies provide essential information, they must also provide good insights into aspects of riders' behavior that affect road safety [8]. However, the demographic variables studied have great potential as moderator variables [9,10]. The variables are not the target of intervention in safety action programs.…”
Section: Introductionmentioning
confidence: 99%
“…Although the studies provide essential information, they must also provide good insights into aspects of riders' behavior that affect road safety [8]. However, the demographic variables studied have great potential as moderator variables [9,10]. The variables are not the target of intervention in safety action programs.…”
Section: Introductionmentioning
confidence: 99%
“…Demographically, the people who engage in these behaviors are generally consistent with the findings described above. Moreover, in situations such as speeding and traffic violations, increased experience has been found to be consistent with increased violations, potentially due to a sense that they understand the road and its hazards better than less experienced drivers ( Trapsilawati et al, 2021 ). Trapsilawati et al (2021) also found that perception or awareness of what consequences the individual could face influence driver behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in situations such as speeding and traffic violations, increased experience has been found to be consistent with increased violations, potentially due to a sense that they understand the road and its hazards better than less experienced drivers ( Trapsilawati et al, 2021 ). Trapsilawati et al (2021) also found that perception or awareness of what consequences the individual could face influence driver behavior. Married drivers with children and older drivers reported increased awareness of legal road requirements, while single and younger drivers were less responsive to these mechanisms, suggesting that risk awareness and aversion may be related to awareness of potential material loss.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the journal, Trapsilawati et al. (2021) look into the underlying predictors of speeding behaviour and examine the effects of demographic variables on the perceived deterrent mechanisms and predict speeding behaviour to target appropriate prevention programmes. Their paper, which focuses on human behaviour in speeding and driving, looked at 212 randomly selected drivers with valid car driving licences and concluded that demographic variables play an important role in drivers’ perceptions towards social and legal sanctions as well as material loss.…”
mentioning
confidence: 99%